Comparison of Two Reciprocating and Anatomical Single File Techniques in Cleaning Oval Anatomies - Krokidis, Andreas; Nicola , Barabanti; Antonio , Cerutti; Panopoulos, Panos (Iranian Endodontic Journal, 2023)
Introduction: The present study aimed to compare the capability of two single-file shaping systems in disinfecting and cleaning long oval root canals. Materials and Methods: Fifty single-rooted teeth were prepared, contaminated with Enterococcus faecalis and divided into two groups. Two samplings were obtained; S1 before chemo-mechanical preparation and S2 after the preparation. Depending on the group, chemo-mechanical preparation was performed with XP-endo Shaper (XPS) and Wave One Gold (WOG). Five teeth from each group were observed under scanning electron microscopy (1000×) to evaluate the cleanliness of root canals at 3, 6 and 9 mm from the apex. All probability (P-values) were two-tailed, statistical significance was set at 0.05 and analyses were conducted using SPSS statistical software. Results: A significant reduction in the colony forming units was observed from S1 to S2 in both tested groups. In S2, XPS group obtained significantly lower colony forming units (P<0.001). In the cleanliness study, XPS group resulted in significantly cleaner canals compared to WOG. Conclusions: Based on this in vitro study XPS system was more effective in disinfecting and cleaning long oval canals.